Experimental Review of Cold Storage for Fishery Products in Aceh Island using Solar Energy - Khairunnas Nas Khairunnas; Ahmad Syuhada; Sarwo Edhy Sofyan (Politeknik Negeri Lhokseumawe, 2023)
Data from the Ministry of Maritime Affairs and Fisheries shows that Aceh Province, with a coastline length of 2666.3 km stretching from east to west, holds a variety of marine wealth, both fisheries and other natural resources. The province of Aceh has archipelagoes spread over Aceh Besar and Aceh Singkil. The archipelago areas in Aceh Besar are Aceh Island, Rice Island and Nasi Island. The availability of electricity in the archipelago, namely on the island of Aceh, is only at 18.00 - 22.00 and 5.00 - 8.00. Because of this, a study was carried out on using solar electricity to drive compressors in cold storage. This study aims to determine the solar energy capacity and photovoltaic area required for cold storage with a capacity of 100 kg of fish, determine the temperature of the cold storage when operating with and without load and determine the coefficient of performance (COP) of cold solar storage over time. This research was conducted experimentally to test the use of cold storage for storing fish. The results showed that the cold storage temperature was -15.9 ℃ with an average current of 0.87 A, a voltage of 226.02 V and a power of 124.72 W when operating without load, while with a load, the temperature was -3.1 ℃ with an average current is 0.890 A, voltage is 225.88 V, and power is 127.96 W. The ideal COP value is greater than the actual COP value (8.07 2.69). To run cold storage using solar energy, a battery with a capacity of 120 Ah is required until it reaches a temperature of -3.1 ℃ lasts 2 – 3 days with 40% remaining battery usage and is recharged every day